Relationship between Stress, Physical Exercise, and Mental Health among Athletes - Aida Mehrad (Universitas Ahmad Dahlan, 2017)
AbstractThe purpose of current literature review is to identify the association between stress, physical exercise, and mental health among athlete. The outcomes of this investigation reveal stress and physical exercise have crucial role on the level of mental health; they likewise can impact on mental health positively and negatively. As well, this study focused on mental health as a main factor among athlete that increase the level of their activities in sports fields. Moreover, lack of attention to this main factor that influenced via stress and physical exercise appeared various results. Therefore, the current paper supports athletes requirements based on two main factors stress and physical exercise to accomplish mental health.Â Keyword:Â Athlete, mental health, physical exercise, stress.